A New Triterpene Glycoside from Fagonia cretica - Imran Anjum, Muhammad; Ahmed, Ejaz; Sharif, Ahsan; Jabbar, Abdul; Malik, Abdul; Hussain, Tajamal; H. Farooqi, Zahoor; Nawaz, Anum (Asian Journal of Chemistry, 2014)
A new triterpene glycoside (fagonoside A) has been isolated from the whole plant of Fagonia cretica. The structures was elucidated on the basis of spectroscopic techniques (1D and 2D NMR, HREIMS, HRFABMS, IR), physical and chemical analysis.